CMB foreground measurements through broad-band radio spectro-polarimetry: prospects of the SKA-MPG telescope. Issue 2 (20th June 2019) - Basu, Aritra; Schwarz, Dominik J; Klöckner, Hans-Rainer; von Hausegger, Sebastian; Kramer, Michael; Wieching, Gundolf; Burkhart, Blakesley
ABSTRACT: Precise measurement of the foreground synchrotron emission, which contaminates the faint polarized cosmic microwave background (CMB) radiation, is a major challenge for the next-generation of CMB experiments. To address this, dedicated foreground measurement experiments are being undertaken at radio frequencies between 2 and 40 GHz. Foreground polarized synchrotron emission measurements are particularly challenging, primarily due to the complicated frequency dependence in the presence of Faraday rotation, and are best recovered through broad fractional-bandwidth polarization measurements at frequencies ≲5 GHz. A unique opportunity for measuring the foreground polarized synchrotron emission will be provided by the 15 m SKA-MPG telescope operating in the frequency range 1.7–3.5 GHz ( S band). Here, we present the scope of a Southern-sky survey in S band at 1 deg angular resolution and explore its added advantage for application of powerful techniques, such as, Stokes Q, U fitting and RM-synthesis. A full Southern-sky polarization survey with this telescope, when combined with other on-going efforts at slightly higher frequencies, will provide an excellent frequency coverage for modelling and extrapolating the foreground polarized synchrotron emission to CMB frequencies (≳80 GHz) with rms brightness temperature better than 10 nK per 1 deg 2 . We find that this survey will be crucial for understanding the effects of Faraday depolarization, especially in low Galactic latitude regions. This will allow better foreground cleaning and thus will contribute significantly in further improving component separation analyses and increase usable sky area for cosmological analysis of the Planck data, and the LiteBIRD mission in the future.